Classificação climática para o Estado do Ceará utilizando distintos sistemas de caracterização - Muniz, Lucas Falcão (2017)
The climatic classifications of Köppen and Thornthwaite are based on precipitation and temperature, where data from the normal climatological published by INMET are traditionally used to estimate this classifications. In this work, for the state of Ceará, it was decided to innovate by incorporating the dense network of rain gauges of FUNCEME spread throughout the state of Ceará and data of average temperature from Climatic Research Unit (CRU). In this way, we investigate in more detail the classifications from more comprehensive data, verifying the correlation between the methods and their sensitivity to the input data. The results indicate that the climatic classification of Köppen presents three climatic types for the state of Ceará (Aw, BSh and BWh), with a predominance of tropical climate with dry winter (Aw), 63% of the State. Thornthwaite, four climatic types (E, D, C1 and C2) were identified, with a predominance of Semiarid climate (D), 85% of the state. Regarding the equivalence of the methods, it was observed low iteration between similar climatic types. However, the results show sensitivity to the input data used for the Thornthwaite classification, and it is possible to delimit small areas that have distinct geographic and physical characteristics of their surroundings, but this was not observed for Köppen.